Sjogren's syndrome - Ankur Jethlia; Vaishali Keluskar; Arvind Shetti (Wolters Kluwer Medknow Publications, 2008)
Sjogren's syndrome (SS) is a chronic autoimmune disorder. It is characterized by dysfunction and destruction of exocrine glands associated with lymphocytic infiltrates and immunological hyperactivity. Salivary and lacrimal glands are the most affected, thus leading to mouth and eye dryness. The disorder can occur alone (it is then known as primary SS) or in association with another autoimmune disease (it is then known as secondary SS). The aim of this article is provide a complete overview of SS.